From Global to Glocal Education: A Bibliometric Study on the Integration of Global Citizenship and Indigenous Culture in Learning Models - Muhammad Rusli; Raden Roro Nanik Setyowati; Akhwani Akhwani; Lalu Habiburrahman; Nurul Aini (Yayasan Pendidikan Bima Berilmu, 2026)
Global education faces persistent challenges in balancing a cosmopolitan orientation with the preservation of local cultural identities. Although Global Citizenship Education (GCE) has developed rapidly, its epistemic integration with indigenous and local cultures in learning models remains fragmented and has not been systematically mapped. This study maps the global research landscape on the integration of GCE and indigenous cultures into learning models through bibliometric analysis. The research employed a Systematic Literature Review (SLR) combined with bibliometric analysis of 600 Scopus-indexed articles from 2010 to 2025, retrieved via Publish or Perish and analyzed using VOSviewer, following a four-phase PRISMA procedure with explicit inclusion and exclusion criteria to ensure transparency and reproducibility. The results reveal a significant increase in publications since 2016, peaking in the 2019-2021 period, followed by a phase of consolidation. Thematic structures are dominated by pedagogical aspects, educational actors, and institutional contexts, while exploration of indigenous cultures remains epistemically peripheral. Geographic analysis shows a pronounced concentration of publications from the Global North. Keyword network analysis indicates a shift from normative discourse toward a more implementation-oriented focus. The findings confirm a structural gap between the intensity of GCE scholarship and the epistemic integration of local cultures. The novelty of this research lies in its comprehensive quantitative mapping that operationalizes glocalization theory within a bibliometric framework, providing an empirical foundation for developing more contextual, equitable, and inclusive glocal learning models. Future research is recommended to pursue qualitative, community-based, and co-creation approaches that operationalize these findings into indigenous-informed pedagogical frameworks.